Bringing Religiosity Back In: critical Reflection on the Explanation of Western Homegrown Religious Terrorism : (Part I) - Dawson, Lorne L. (Perspectives on terrorism, 2021)
An unusual feature of the social scientific study of religious terrorism is the erasure of religiosity as a significant motivational factor. This article systematically delineates and criticizes the presence of this peculiar interpretive preference, demonstrating that it is methodologically suspect and theoretically and empirically unhelpful. There are two parts to the critique. Part I (this article), discusses three foundational aspects of the argument: (1) it delineates ten conditions of the critique, to avoid predictable misunderstandings; (2) it specifies three methodological reasons for considering the motivational claims of religious terrorists as potentially important and valid data; and (3) it surveys the history of the study of religious terrorism to identify some extra-methodological influences that may have truncated the analysis of the religious motivations for religious terrorism. Part II (the next article), examines three types of arguments commonly used to minimize the role of religiosity in motivating religious terrorism. Identifying the arguments by the primary interpretive errors they rely on, some arguments (1) mistakenly treat the religious background and knowledge of homegrown jihadists as a sound indicator of their religiosity; others (2) inappropriately apply a modern Western normative conception of religion to homegrown jihadists; and some arguments (3) rely on an overly dichotomized conception of the relationship of social processes and ideology in the process of radicalization. The critique ends with consideration of alternative perspectives, offering a more refined conception of the role of ideology, and more specifically religiosity, in the determination of the actions of religious terrorists.